Application of Target Costing in Management of Production Costs to Optimize Profits at UMKM Brownice Manado - George Evander Kumaat; Jenny Morasa; I Gede Suwetja (PT FORMOSA CENDEKIA GLOBAL, 2023)
There are several methods of determining production costs. One of them is the Target Costing method. Target Costing is a method for determining the production cost of a product based on the selling price. The goal of the company using the Target Costing method itself is to reduce production costs from the total existing production costs so that the company can increase profits as expected without the need to increase the price of the product. This study aims to analyze whether the application of the Target Costing method in managing production costs at UMKM Brownice Manado can optimize profits as expected. This research was conducted using a qualitative descriptive method and was carried out at Brownice SMEs in the city of Manado from April to May 2022. The results of this study indicate that by using the Target Costing method, the required production costs can be minimized so that the profits obtained can be further optimized accordance with the company's expectations without increasing the price of the product. That way the conclusion is that the Target Costing method can be an alternative for UMKM Brownice in setting production costs.